The Effect of Special Exercises in the Diamond Style in Some Physiological Variables and the Basic Skills of Futsal Players - Abbas Mahdi Saleh (Journal of Global Pharma Technology, 2018)
As the importance of research in the preparation of special exercises and knowledge of their impact in some physiological variables and basic skills of futsal players. The problem of research: researchers see the problem of research is slow to move the player of the station from the attack to defend when the loss of the ball and this generates pressure by the opposing team because of the numerical increase of the players of the opposing team, especially in the case of possession of the ball begins to weaken in this style of midfield Will cause serious problems in defending the goal of the team and will work researchers put physical exercises and skills to develop the basic skills, variables and physiology to promote the reality and development of this method.Research ObjectivesPreparation of exercises in the style of diamond for futsal players.To identify the effect of the exercises in the diamond style in some physiological variables and the basic skills of futsal players.Research HypothesisThere is an impact of the exercises in the diamond style in some physiological variables and the basic skills of futsal players.As for the research methodology and its field procedures, researchers used the experimental method to solve the problem of research. The research society was determined by the players of the University of Kufa for the halls of futsal, and they were divided into two groups (experimental and control) in the simple random way (Lottery).As for the most important conclusions and recommendations, the most important conclusions are the following:The exercise of the diamond method helped to develop some physiological variables (the concentration of lactic acid, the enzyme L.D.H) in the members of the experimental group.Diamond-style exercises have helped to develop the basic skills of members of the futsal group of the gyms.The main recommendations included the following:Recommend the researchers to pay attention to the use of special exercises in accordance with the diamond style when training the futsal players.Researchers recommend conducting similar studies on different age groups.Keywords: Special exercises, Diamond style, Physiological variables and basic skills.